2014
DOI: 10.1002/ange.201310923
|View full text |Cite
|
Sign up to set email alerts
|

EBC‐219: A New Diterpene Skeleton, Crotinsulidane, from the Australian Rainforest Containing a Bridgehead Double Bond

Abstract: EBC-219 (4), isolated from Croton insularis (Baill), was established by spectroscopic and DFT methods as the first member of a new diterpene skeletal class, uniquely defined by the presence of a bicyclo[10.2.1] bridgehead olefin. The proposed biogenetic pathway to 4 from the co-isolated natural products EBC-131 (1), EBC-180 (2) and EBC-181 (3) is highly likely. EBC-180 (2) and EBC-181 (3) showed moderate to strong cytotoxic activity against various cancer cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The solitary entry in this section was discovered only very recently by Reddell, Parsons, and Williams in the stems of Croton insularis (Baill) in a campaign aimed at discovering new anti-cancer agents from the Australian rainforest, in collaboration with EcoBiotics Ltd. [16] The structure of the bicyclo[10.2.1]pentadec-2,6,13-triene ring system of EBC-219 (137; Scheme 8) was determined by NMR spectroscopy, specifically through the observation of key HMBC correlations. DFT calculations indicated that four low-energy conformations could be adopted by the macrocyclic ring system.…”
Section: 1] Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The solitary entry in this section was discovered only very recently by Reddell, Parsons, and Williams in the stems of Croton insularis (Baill) in a campaign aimed at discovering new anti-cancer agents from the Australian rainforest, in collaboration with EcoBiotics Ltd. [16] The structure of the bicyclo[10.2.1]pentadec-2,6,13-triene ring system of EBC-219 (137; Scheme 8) was determined by NMR spectroscopy, specifically through the observation of key HMBC correlations. DFT calculations indicated that four low-energy conformations could be adopted by the macrocyclic ring system.…”
Section: 1] Systemsmentioning
confidence: 99%
“…[15] Furthermore, and perhaps even more importantly, we had recently isolated a novel natural product that contained a bridgehead double bond, and therefore wanted to better understand the application of Bredts rule to natural product systems. [16] In consideration of the above and the fact that it was Bredts century-old work on the camphene and pinane natural product series that resulted in the formulation of the rule, it seemed fitting to review this special class of natural products for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…This method unequivocally predicts all known natural products having bridgehead double bonds to be ''isolable,'' providing a powerful tool for assignment of natural products containing bridgehead double bonds. 28 Since it first emerged in the 1980s, hundreds of natural products with a bridgehead double bond have been isolated by the phytochemists, such as the famous taxol, CP molecules, the newly identified EBC-219, 29 mangelonoid A, 30 brassicicene M, 31 schiglautone A, 32 and others [33][34][35][36][37] (Figure 2). Due to their noticeable complexity, with different ring strain energy in the skeleton (Fawcett's S value highlighted in blue in Figure 2), and promising bioactivity, these natural products have attracted considerable research attention and large sections of them have been synthesized using different strategies.…”
Section: Introductionmentioning
confidence: 99%